Machine learning-enabled computer vision for plant phenotyping a primer on AI/ML and a case study on stomatal patterning - Tan, Grace D (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology.